(untitled) (Journal of Hama University, 2022)
Normal-grown Ballade hens (DW-) and Normal-grown Ballade hens produced by intermarrying Normal-grown rooster (DWDW), and hens which have a recessive sex Linked dwarfing gene (dw-), were cared in cages in a coop of the open model. The results indicate that the age of sexual maturity of Normal-grown Ballade hens (DW-) produced by dwarf hens (dw-) was no significantly. It has decrease 4 days compared to hens produced by Normal-grown hens (DW-). The Normal-grown Ballade hens produced by dwarf hens (dw-) during the egg production period from 21 to 37 weeks showed an increase in the average daily egg production by 0.04 eggs per day per hen (p<0.05), and a statistically significant increase in the average egg weight, the difference was estimated with an average egg weight of 2.1 g, While the consumption of feed per hen decreased Ballade hens produced by dwarf hens (dw-) significantly by 3 g/day, which resulted in a significant decrease in the amount of feed consumption to produce a kilogram of eggs by 50 g, The mass of eggs produced by Normal-grown Ballade hens produced by dwarf hens (dw-) was significantly increased by 20 g compared to hens produced by Normal-grown hens (DW-),